Intense Molar Circular Dichroism in Fully Conjugated All‐Carbon Macrocyclic 1, 3‐Butadiyne Linked pseudo‐meta [2.2]Paracyclophanes. Issue 53 (9th September 2022) - Sidler, Eric; Zwick, Patrick; Kress, Charlotte; Reznikova, Ksenia; Fuhr, Olaf; Fenske, Dieter; Mayor, Marcel
Abstract: Invited for the cover of this issue is the group of Marcel Mayor at the University of Basel with co‐workers Olaf Fuhr and Dieter Fenske from Karlsruhe Institute of Technology. The image depicts the studied all‐carbon polygon shaped macrocycles along with their intense circular dichroism spectra in the background. The bright light within the macrocycles displays its efficient conjugation. Read the full text of the article at 10.1002/chem.202201764 . Abstract : " The introduction of pseudo‐ meta PCPs into carbon‐based macrocycles allowed us to obtain four enantiopure polygon‐shaped structures in high yield, displaying unprecedented large molar circular dichroism values for all‐carbon macrocycles and high absorption dissymmetry factors." This and more about the story behind the front cover can be found in the article at 10.1002/chem.202201764 ).